Roles of STAT3 and ZEB1 Proteins in E-cadherin Down-regulation and Human Colorectal Cancer Epithelial-Mesenchymal Transition - Xiong, Hua (American Society for Biochemistry and Molecular Biology, 2012)
The progression of colorectal carcinoma (CRC) to invasive and metastatic disease may involve localized occurrences of epithelial-mesenchymal transition (EMT). However, mechanisms of the EMT process in CRC progression are not fully understood. We previously showed that knockdown of signal transducer and activator of transcription 3 (STAT3) up-regulated E-cadherin (a key component in EMT progression) in CRC. In this study, we examined the roles of STAT3 in CRC EMT and ZEB1, an EMT inducer, in STAT3-induced down-regulation of E-cadherin. Knockdown of STAT3 significantly increased E-cadherin and decreased N-cadherin and vimentin expressions in highly invasive LoVo CRC cells. Meanwhile, overexpression of STAT3 significantly reduced E-cadherin and enhanced N-cadherin and vimentin expressions in weakly invasive SW1116 CRC cells. Activation of STAT3 significantly increased CRC cell invasiveness and resistance to apoptosis. Knockdown of STAT3 dramatically enhanced chemosensitivity of CRC cells to fluorouracil. STAT3 regulated ZEB1 expression in CRC cells, and the STAT3-induced decrease in E-cadherin and cell invasion depended on activation of ZEB1 in CRC cells. Additionally, pSTAT3(Tyr-705) and ZEB1 expressions were significantly correlated with TNM (tumor, lymph node, and metastasis stages) (p < 0.01). In conclusion, STAT3 may directly mediate EMT progression and regulate ZEB1 expression in CRC. ZEB1 may participate in STAT3-induced cell invasion and E-cadherin down-regulation in CRC cells. The expressions of pSTAT3(Tyr-705) and ZEB1 may be positively associated with CRC metastasis. Our data may provide potential targets to prevent and/or treat CRC invasion and metastasis.